Flowers anticipate revisits of pollinators by learning from previously experienced visitation intervals. (3rd June 2019) - Mittelbach, Moritz; Kolbaia, Sandro; Weigend, Maximilian; Henning, Tilo
ABSTRACT: Plants – and their pollinating counterparts – display complex and sophisticated mechanisms to achieve successful pollination. It probably was only a matter of time for proof of plant intelligence in the context of floral ecology to surface, i.e. the memorization of previous events and a corresponding adjustment of flower behavior. In a recent study we presented a large experimental dataset on the evolution of stamen movement patterns observed in Loasaceae and the apparent role of plant behavior in the diversification of this plant group. The findings at species level suggest that individual plants may be able to adjust the timing of their pollen presentation to the actual pollination scenario they experience. Here we provide first evidence for a pre-emptive stamen presentation in Nasa poissoniana (Loasaceae), based on previously experienced pollinator visitation intervals. Using the unique ability of fast and precise stamen movements in response to a previous stimulus of the nectar scales, the plants should be able to reduce pollen loss and increase outbreeding success via optimizing the timing of male function. We discuss this behavior and its implications in the light of the recent literature and propose questions for future investigations.